2020
DOI: 10.5398/tasj.2020.43.3.263
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Accuracy Improvement of Indonesian Dairy Cattle Fiber Feed Compositions Using Near-Infrared Reflectance Spectroscopy Local Database

Abstract: The accuracy of near infrared reflectance spectroscopy (NIRS) depends on the database generated from the conventional wet chemistry (CWC). Currently, the local database of fiber-source feeds for tropical dairy cattle are still limited. The study aimed to compare CWC and NIRS initial database (NIRSID) results, to predict CWC from NIRSID, and to improve the accuracy of NIRS prediction using local database (NIRSLD). Five feeds as sources of fiber (Napier grass, natural grass, corn leaves, corn husk, and rice stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
1
20
4
1
Order By: Relevance
“…The validation failed to improve the prediction accuracy. R 2 and RPD found in this study were lower than the result found by Despal et al (2020) for forage quality estimation or Coppa et al (2014) in fresh and thawed milk.…”
Section: Milk Fatty Acids Estimation Using Ft-nirscontrasting
confidence: 88%
See 3 more Smart Citations
“…The validation failed to improve the prediction accuracy. R 2 and RPD found in this study were lower than the result found by Despal et al (2020) for forage quality estimation or Coppa et al (2014) in fresh and thawed milk.…”
Section: Milk Fatty Acids Estimation Using Ft-nirscontrasting
confidence: 88%
“…The higher PUFA/SFA value is found in smallholder dairy farm milk due to the high proportion used of forage (50%) in the ration (Lestari et al, 2015), which contain high PUFA (Collomb et al, 2001). The average LCFA found in the milk from traditional farms was 82.25% which shows a great body storage mobilization (Collomb et al, 2001) due to low nutrient content in the feed, primarily forage (Despal et al, 2020). The average CLA content in the milk sample was 1.360%, higher than the average content of CLA in cow's milk (0.34 -1.07%) (Fritsche et al, 2000).…”
Section: Milk Fatty Acid Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pengujian sampel menggunakan NIRS (near infrared reflectance spectroscopy) sehingga didapatkan data kandungan bahan kering (BK), abu, protein kasar (PK), serat kasar (SK), serat diterjen netral (NDF), dan serat diterjen asam (ADF) pada pakan serat [15].…”
Section: Analisis Kandungan Nutrienunclassified